Effects of exercise on cancer patients suffering chemotherapy-induced peripheral neuropathy undergoing treatment: A systematic review. (January 2018) - Duregon, Federica; Vendramin, Barbara; Bullo, Valentina; Gobbo, Stefano; Cugusi, Lucia; Di Blasio, Andrea; Neunhaeuserer, Daniel; Zaccaria, Marco; Bergamin, Marco; Ermolao, Andrea
Highlights: Chemotherapy treatment induces in cancer patients a huge number of side effects, such as Peripheral Neuropathy. Physical exercise is feasible for cancer patients and can counteract the limitations due to chemotherapy. A specific exercise protocol produces significant improvements in cancer patients with Peripheral Neuropathy. Abstract: Background: Chemotherapy-induced peripheral neuropathy (CIPN) is the most common neurological and clinically relevant side effect of many commonly used chemotherapeutic agents. Moreover, little effort has been done to investigate the potentially beneficial effects of specific exercises to counteract the CIPN symptoms. Objective: This document aims to summarize and analyze systematically the current body of evidence about the effects of specific exercise protocols on CIPN symptoms, balance control, physical function and quality of life in patients with CIPN. Literature survey: Specific terms were identified for the literature research in MEDLINE, Scopus, Bandolier, PEDro, and Web of Science. Methodology: Five manuscripts were considered eligible for this review. Quality appraisal distinguished two studies as high quality investigations while three with low quality. Results were summarized in the following domains: "CIPN symptoms", "Static balance control", "Dynamic balance control", "Quality of life and Physical function". Synthesis: Significant improvements were detected on postural control. Additionally, patients' quality of life and independence were found ameliorated after exercise sessions. Combined exercise protocols including endurance, strength and sensorimotor training showed larger improvements. Conclusions: This systematic review comes from a highly selected but small source of data. Nevertheless, specific exercise for cancer patients undergoing chemotherapy with CIPN symptoms should be recommended since these interventions appeared as feasible and have been demonstrated as useful tools to counteract some of the limitations due to chemotherapy.